Mejoramiento genético y actividades relacionadas. Actividades relacionadas. Africa. Africa oriental - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Detailed information is presented on the activities of the Eastern Africa regional bean program. This regional project covers Ethiopia, Kenya, Somalia, and Uganda. CIAT's regional activities aim primarily at strengthening national capabilities to conduct research relevant to small farmers' needs. Special attention is being given to training, both at CIAT and in Africa. Each country's var. development program is being strengthened by access to a wider range of germplasm. (CIAT)